Dislocation distribution in ruby single crystals under loading at high temperatures - Bosin, M.E.; Zvyagintseva, I.F.; Zvyagintsev, V.N.; Lavrentyev, F.F; Nikiforenko, V.N. (Functional Materials, 2004)
Evolution of dislocation structure in ruby single crystals under four-point bending at T = 1490°C has been studied using the etch pit method. The small-angle substructure boundaries have been observed, the dislocation types have been identified and their densi -ties have been measured. The screw and edge dislocation _density has been shown to be distributed symmetrically about the sample neutral axis [1100]] and about the [0001] one. The starting shear stress has been first measured and found to be 200 MPa in the prismatic slip system. This value is associated with the friction stress of the crystal lattice, that is, with the Peierls-Nabarro stress value in the (1100) prism plane along the [1120] direction. The starting stress value is to be known to treat thermomechanically high-perfection ruby single crystals and to solve the problem of long-term laser stability.